2020
DOI: 10.3390/nu12051275
|View full text |Cite
|
Sign up to set email alerts
|

Progressive Metabolic Dysfunction and Nutritional Variability Precedes Necrotizing Enterocolitis

Abstract: Necrotizing Enterocolitis (NEC) is associated with prematurity, enteral feedings, and enteral dysbiosis. Accordingly, we hypothesized that along with nutritional variability, metabolic dysfunction would be associated with NEC onset. Methods: We queried a multicenter longitudinal database that included 995 preterm infants (<32 weeks gestation) and included 73 cases of NEC. Dried blood spot samples were obtained on day of life 1, 7, 28, and 42. Metabolite data from each time point included 72 amino acid (AA) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 26 publications
0
33
0
Order By: Relevance
“…Specifically, review of the literature revealed 15 clinical studies reporting on metabolomics and proteomics potential in discovering NEC biomarkers published within the last 11 years. Among them, five studies dealt with metabolomics (104,107,109,111,112), six with proteomics (82,88,(101)(102)(103)110), while four studies integrated metabolomics with either proteomics (one study) (105) or metagenolics (three studies) (87,106,109). A total of 349 infants with either suspected or definite NEC, 147 infants with sepsis/NEC, and 1,164 matched controls were included ( Table 2).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Specifically, review of the literature revealed 15 clinical studies reporting on metabolomics and proteomics potential in discovering NEC biomarkers published within the last 11 years. Among them, five studies dealt with metabolomics (104,107,109,111,112), six with proteomics (82,88,(101)(102)(103)110), while four studies integrated metabolomics with either proteomics (one study) (105) or metagenolics (three studies) (87,106,109). A total of 349 infants with either suspected or definite NEC, 147 infants with sepsis/NEC, and 1,164 matched controls were included ( Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…A total of 349 infants with either suspected or definite NEC, 147 infants with sepsis/NEC, and 1,164 matched controls were included ( Table 2). The most commonly used specimens for omics analysis were urine in five studies (87,103,104,111,112), stool in four studies (103,105,108,109), and plasma/serum in four studies (101,105,107,110), while surgically excised intestinal/colon tissues, dry blood spots, and buccal swabs each was used in one study, respectively (88,102,112). These studies detected several molecules that differed significantly between NEC cases and controls.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Both antibiotic treatment and NEC progression can alter the composition of the gut microbiome and its metabolism [10,11], in turn affecting the host metabolism and circulating metabolites in preterm infants [12], including amino acid and lipid derivatives [13,14].…”
Section: Introductionmentioning
confidence: 99%